2013
DOI: 10.1037/a0033751
|View full text |Cite
|
Sign up to set email alerts
|

Psychological processes and repeat suicidal behavior: A four-year prospective study.

Abstract: Objective: Although suicidal behavior is a major public health concern, understanding of individually sensitive suicide risk mechanisms is limited. In this study, the authors investigated, for the first time, the utility of defeat and entrapment in predicting repeat suicidal behavior in a sample of suicide attempters. Method: Seventy patients hospitalized after a suicide attempt completed a range of clinical and psychological measures (depression, hopelessness, suicidal ideation, defeat, and entrapment) while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
114
1
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(132 citation statements)
references
References 44 publications
(69 reference statements)
10
114
1
3
Order By: Relevance
“…According to Gilbert and colleagues, this involuntary subordination and resulting negative affect could potentially lead to suicidal thoughts and actions [39]. Such an explanation is consistent with the Integrated Motivational-Volitional (IMV) Model of suicidal behaviour which maps out the process from defeat and entrapment to suicidal thoughts and behaviours [4,27].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…According to Gilbert and colleagues, this involuntary subordination and resulting negative affect could potentially lead to suicidal thoughts and actions [39]. Such an explanation is consistent with the Integrated Motivational-Volitional (IMV) Model of suicidal behaviour which maps out the process from defeat and entrapment to suicidal thoughts and behaviours [4,27].…”
Section: Discussionmentioning
confidence: 73%
“…Consequently, if an individual perceives no escape or rescue from the situation, suicidal ideation emerges. More recently, defeat and entrapment have been shown to be important factors in understanding suicidal thoughts and actions [25] and self-harm [26] cross-sectionally and over time [27,28].…”
Section: How Are Social Comparisons Related To Suicidal Outcomes?mentioning
confidence: 99%
“…The volitional phase factors govern the transition from suicidal thinking to suicidal behaviour and include access to the means of suicide, the personal capacity for carrying out suicide and impulsivity [1,43] There is growing evidence in supports of the IMV model with several studies having yielded support for the central tenets of the model. Higher levels of defeat are associated with suicide ideation [47] and entrapment, defined as blocked attempts to escape from high stress or defeating circumstances, was found to be the most important modifiable predictor of repeat suicidal behaviour four years after a previous attempt [48]. Other studies have demonstrated that volitional phase factors are key to the emergence of suicidal behaviour, like impulsivity [49] and access to means [50,51].…”
Section: Integrated Motivational-volitional (Imv) Model Of Suicidal Bmentioning
confidence: 92%
“…They experienced tunnel vision and could not see or comprehend any other solution to solve their problems [14].…”
Section: Suicide From the Perspective Of Those Whom Have Survived A Smentioning
confidence: 99%